Static and Dynamic Magnetic Properties of Circular and Square Cobalt Nanodots in Hexagonal Cells - Escrig-Murua, J; Saavedra-Díaz, E (Royal Society of Chemistry, 2024)
In this work we performed a detailed numerical analysis to investigate the static and dynamic magnetic properties of hexagonal cells of square and circular cobalt nanodots as a function of the distance between them and the external magnetic field to which they are subjected. By simulating hysteresis curves with the external magnetic field applied parallel and perpendicular to the plane of these nanostructures, we can conclude that the cobalt nanodots presented a significant perpendicular magnetic anisotropy. We also obtained that the coercivity increases with decreasing volume, which implies that the circular dots have a higher coercivity than the square dots. Furthermore, we studied the dynamic susceptibility of these systems and found that it is possible to control both the position and the number of resonance peaks by controlling the geometry and the distance between the magnetic nanodots. This work provides useful information on the behaviour of cobalt nanodot arrays, opening paths for the design and improvement of two-dimensional technological devices. © 2024 The Royal Society of Chemistry.